Evaluating general practitioners’ focused lung ultrasound competence and findings in patients with suspected community-acquired pneumonia in general practice - Julie Jepsen Strøm; Camilla Aakjær Andersen; Martin Bach Jensen; Janus Laust Thomsen; Christian B. Laursen; Søren Helbo Skaarup; Hans Henrik Lawaetz Schultz; Malene Plejdrup Hansen (Scandinavian Journal of Primary Health Care)
Objectives To evaluate general practitioners’ (GPs’) ability to perform focused lung ultrasound (FLUS) following a training program and assess FLUS feasibility in general practice. Also, to describe FLUS findings and evaluate GPs’ ability to interpret these in adults with acute lower respiratory tract infection (LRTI) when pneumonia is suspected and assess GPs’ perception of FLUS impact.Methods Nine GPs, using point-of-care ultrasound, completed a FLUS training program. Adults (≥ 18 years) with acute cough (< 28 days) and at least one other symptom of acute LRTI, where the GP suspected pneumonia, were subsequently included. All patients received FLUS. The GPs reported FLUS findings, feasibility, and perception of FLUS impact. Recorded FLUS videos from all patients were reviewed by two specialists (Specialist Reference). The specialists assessed FLUS image quality. Agreements between the GPs and the Specialist Reference on FLUS findings were used to evaluate GPs’ ability to interpret FLUS.Results Of 91 patients included, FLUS image quality was acceptable or higher in 84 patients (92.4%). FLUS proved feasible with only two scans not completed. The GPs reported FLUS pathological findings in 51.7% of patients in 78% agreement with the Specialist Reference and Cohen’s kappa 0.56. Focal B-lines represented the most frequent pathological findings. The GPs perceived that FLUS impacted change in tentative diagnosis and/or plans for treatment and/or visitation in 29 (32.0%) of patients.Conclusion After the training, the GPs performed FLUS well. Interpretation of FLUS pathology presence was of moderate agreement. The GPs perceived that FLUS had impact on patient management.Trial registration number ClinicalTrials.gov NCT04711031